Improving Provision of Expedited Partner Therapy in the Obstetrics and Gynecology Office [A131]. (May 2022) - Vasudeva, Isha; Hartnett, Janice M.; Bondi, Laura; Newmark, Alexis; Lindsay, Sarah
Abstract : INTRODUCTION: Expedited partner therapy (EPT) provides an opportunity to treat partners of patients diagnosed with gonorrhea or chlamydia without an examination, a practice supported by the American College of Obstetricians and Gynecologists and the Centers for Disease Control and Prevention (CDC), to decrease the risk of reinfection. However, EPT is not consistently offered by all providers. We performed a quality improvement project to increase the rate at which EPT is offered and prescribed at our clinic in line with Department of Public Health (DPH) regulations. METHODS: We completed quality improvement interventions at the Women's Ambulatory Health Services, an urban hospital-based outpatient clinic in Hartford, CT, to improve appropriate provision of EPT to 70% of eligible patients. We defined appropriate provision of EPT by infection type (gonorrhea or chlamydia only, per CDC guidelines) and method of EPT prescription per DPH regulations (paper prescription or in-clinic dispensing to a patient for EPT). Interventions included education sessions regarding state EPT policies, implementation of a standard clinic workflow, and pre-completed written prescriptions. We gathered data from the electronic health record over 18 months to assess our quality improvement outcome. RESULTS: Rates of appropriate provision of EPT improved with our interventions (22% versus 75%). We found an unexpected decrease in EPT acceptance by patients after initiation of our interventions (81% versus 50%). CONCLUSION: Our quality improvement intervention increased appropriate provision of EPT. However future work should investigate potential barriers to EPT acceptance, including the impact of DPH regulation of prescribing options and standard workflow in patient counseling.